Comparison of different models for high damping rubber bearings in seismically isolated bridges. Issue 104 (January 2018) - Tubaldi, E.; Mitoulis, S.A.; Ahmadi, H.
Abstract: Steel-reinforced high damping natural rubber (HDNR) bearings are widely employed in seismic isolation applications to protect structures from earthquake excitations. In multi-span simply supported bridges, the HDNR bearings are typically placed in two lines of support, eccentric with respect to the pier axis. This configuration induces a coupled horizontal-vertical response of the bearings, mainly due to the rotation of the pier caps. Although simplified and computationally efficient models are available, which neglect the coupling between the horizontal and vertical response, their accuracy has not been investigated to date. In this paper, the dynamic behaviour and seismic response of a benchmark three-span bridge are analysed by using an advanced HDNR bearing model recently developed and capable of accounting for the coupled horizontal and vertical responses, as well as for significant features of the hysteretic shear response of these isolation devices. The results of the analyses shed light on the importance of the bearing vertical stiffness and how it modifies the seismic performance of isolated bridges. Successively, the seismic response estimates obtained by using simplified bearing models, whose use is well established and also suggested by design codes, are compared against the corresponding estimates obtained by using the advanced bearing model, to evaluate their accuracy for the current design practice. Highlights: Seismic response of isolated MSSS bridges with emphasis on HDNR bearings axial effects. Importance of the coupling between bearing horizontal and vertical response. Influence of soil structure interaction effects on bearing behaviour. Comparison between advanced and simplified bearing models.